Pengaruh Penggunaan Bahasa Prokem Terhadap Eksistensi Bahasa Indonesia di Kalangan Mahasiswa Pendidikan Geografi Universitas Negeri Medan - Yenni Lestari Sitompul; Qamara Aulia Ananda; Lili Tansliova (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This research was conducted by describing what happened in the field regarding the use of prokem language among students and the existence of Indonesian language at this time. The first research objective is the reason students use prokem language, secondly how often students use prokem language, thirdly the impact of using prokem language on the existence of Indonesian language. The research method used is descriptive qualitative method with data collection techniques in the form of interviews with students majoring in geography education at Medan State University, observation and literature study to provide supporting data from the analysis of data obtained in the field. The results and discussion obtained that students today are very often using prokem language in daily communication and in the campus environment, the reason they use prokem language is because they want to be up to date and follow current trends. The negative impact of prokem language results in a decrease in the existence of good and correct Indonesian in today's society and this also has a negative impact on the quality of writing and speaking of students as an academic